Pluggable optical transceiver:market and technology - VG KOZLOV (Dianxin kexue)
Pluggable optical transceivers provide a practical,standard optoelectronic interface solution for a variety of optical networks.Firstly,a variety of 10 Gbit/s optical transceivers were shown,and then the global optical transceiver market was classified according to device technology.The average selling price of ONU in FTTx,ONU optical modules in DWDM networks,Ethernet and FTTx and 100GbE SR4 and CWDM4 transceivers were revealed.Finally,the onboard optical module packaged with the ASIC switch was given.